Intensive care doctors' preferences for arterial oxygen tension levels in mechanically ventilated patients. Issue 10 (21st June 2018) - Schjørring, O. L.; Toft‐Petersen, A. P.; Kusk, K. H.; Mouncey, P.; Sørensen, E. E.; Berezowicz, P.; Bestle, M. H.; Bülow, H.‐H.; Bundgaard, H.; Christensen, S.; Iversen, S. A.; Kirkeby‐Garstad, I.; et al.
Abstract : Background: Oxygen is liberally administered in intensive care units (ICUs). Nevertheless, ICU doctors' preferences for supplementing oxygen are inadequately described. The aim was to identify ICU doctors' preferences for arterial oxygenation levels in mechanically ventilated adult ICU patients. Methods: In April to August 2016, an online multiple‐choice 17‐part‐questionnaire was distributed to 1080 ICU doctors in seven Northern European countries. Repeated reminder e‐mails were sent. The study ended in October 2016. Results: The response rate was 63%. When evaluating oxygenation 52% of respondents rated arterial oxygen tension (PaO2 ) the most important parameter; 24% a combination of PaO2 and arterial oxygen saturation (SaO2 ); and 23% preferred SaO2 . Increasing, decreasing or not changing a default fraction of inspired oxygen of 0.50 showed preferences for a PaO2 around 8 kPa in patients with chronic obstructive pulmonary disease, a PaO2 around 10 kPa in patients with healthy lungs, acute respiratory distress syndrome or sepsis, and a PaO2 around 12 kPa in patients with cardiac or cerebral ischaemia. Eighty per cent would accept a PaO2 of 8 kPa or lower and 77% would accept a PaO2 of 12 kPa or higher in a clinical trial of oxygenation targets. Conclusion: Intensive care unit doctors preferred PaO2 to SaO2 in monitoring oxygen treatment when peripheral oxygen saturation was not included in the question. The identification of PaO2 as the preferred target and the thorough clarification of preferences are important when ascertaining optimal oxygenation targets. In particular when designing future clinical trials of higher vs lower oxygenation targets in ICU patients.